The Influence of the Independent Entrepreneurship Program on the Entrepreneurial Skills of EduBlankOn Participants at Universitas Negeri Yogyakarta - Permatasari, Berliana; Safuri Musa; Uum Suminar (Journal of Nonformal Education and Community Empowerment, 2024)
This study aims to determine the effect of the independent entrepreneurship program on the entrepreneurial skills of EduBlankOn participants at Universitas Negeri Yogyakarta. This research uses a quantitative approach. The method used in this research is correlation with a probability sampling technique (random sample). The data collection techniques used were questionnaires and documentation. From the results of the study, it is known that the t value is 12,137 with a Sig value. 0.002 <0.05, which means that there is a positive influence of the independent entrepreneurship program on entrepreneurial skills. Furthermore, from the coefficient of determination test, the value (R Square) is 43.1%, meaning that the independent entrepreneurship program has an influence of 43.1% on entrepreneurial skills. So it is concluded that there is a significant positive influence of the independent entrepreneurship program on the entrepreneurial skills of EduBlankOn participants at Universitas Negeri Yogyakarta